CERTAIN MECHANICAL ASPECTS IN COMPARATIVE CONTINENTAL RIFTING WITH A SPECIAL REFERENCE TO THE BAIKAL RIFT - Bahat D. (My University, 1981)
In the Baikal rift fracture initiation, propagation and bifurcation occurred under energy conditions considerably higher than in other continental rifts. The brittle fracture of this rift was strongly influenced by the adjacent Siberian platform. Comparative continental rifting suggests that rift initiation reflects local mantle rather than regional crustal conditions. Three aspects related to fault bifurcation in rifts include intensity and repetition of branching, as well as displacement along branching planes; the three should be distinguished.